Dissolution of Pt and Its Temperature Dependence in Anhydrous Acetonitrile- and Methanol-Based Electrolytes - Ranninger, Johanna; Nikolaienko, Pavlo; Wachs, Susanne; Möller, Jonas; Mayrhofer, Karl; Berkes, Balázs (Journal of The Electrochemical Society, 2020)
Electrode stability is a crucial performance criterion in electrochemistry. Interestingly, in certain fields of electrochemistry, especially when using nonaqueous electrolytes, like in electroorganic synthesis, this aspect remained largely out of focus of investigations so far. Regarding the handling and particularly the purification of nonaqueous electrolytes and the applicable analytical methods to study stability, such fundamental investigations are usually more complicated than in aqueous electrolytes. Herein, we present stability data of Pt metal, as one of the most frequently used electrodes in electroorganic synthesis, in anhydrous (ppm level) acetonitrile- and methanol-based electrolytes in the usually applied potential ranges, obtained using an electroanalytical flow cell (EFC) coupled to an inductively coupled plasma mass spectrometer (ICP-MS). Both electrolyte solvents are widely used in nonaqueous electrochemistry and possess different physico-chemical properties. Here we chose them as representative examples of aprotic and protic solvents and as solvent molecules with two different electrochemical activities: acetonitrile with a wide stability window and methanol being a rather easily oxidizable molecule. A temperature study reveals not only the different electrochemical behavior of the electrolyte systems but also significant differences in Pt dissolution in the studied electrolytes.
CRIS-Team WoS Importer:2020-09-25